Commemorating the 10th Anniversary of Al-Iqtishad Journal of Islamic Economics: A Bibliometric Analysis - Ujang Syahrul Mubarrok; Raditya Sukmana; Ririn Tri Ratnasari (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2020)
Abstract. This study bibliometrically evaluates and analyzes the articles published by Al-Iqtishad Journal in the last ten years. Data were obtained from the website of Al-Iqtishad Journal and further edited in Mendeley. The results show that the Al-Iqtishad journal had published 215 articles in the last ten years, mostly in English and Indonesian languages, with the majority of the topics on Islamic banking. These findings tend to be useful for the editorial board of Al-Iqtishad journal to evaluate and improve the publication of their articles. Keywords: Islamic Economics; Bibliometrics Abstrak. Studi ini menganalisis dan mengevaluasi secara bibliometrik artikelartikel yang diterbitkan oleh Jurnal Al-Iqtishad dalam 10 tahun terakhir. Data diperoleh dari situs web dan selanjutnya diedit di Mendeley. Hasil penelitian menunjukkan bahwa jurnal Al-Iqtishad telah menerbitkan 215 artikel dalam sepuluh tahun terakhir yang sebagian besar berbahasa Inggris dan Indonesia, dengan mayoritas topik tentang perbankan syariah. Temuan ini cenderung bermanfaat bagi dewan redaksi Iqtishad untuk mengevaluasi dan meningkatkan publikasi artikel mereka.Kata kunci: Ekonomi Islam; Bibliometrik